Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1007/bf02636185
|View full text |Cite
|
Sign up to set email alerts
|

Heats of combustion of fatty esters and triglycerides

Abstract: Gross heats of combustion (HG) have been measured for three classes of fatty esters and two classes of triglycerides (TGs). The esters included saturated methyl esters, Me 6:0–22:0; saturated ethyl esters, Et 8:0–22:0; and unsaturated methyl esters, Me 12:1–22:1, Me 18:2 and Me 18:3. The TGs included the saturated TGs, C 8:0–22:0, and unsaturated TGs, C 11:1, C 16:1, C 18:1, C 18:2, C 18:3, C 20:1 and C 22:1. HG were measured in a Parr adiabatic calorimeter according to a modification of ASTM D240 and D2015. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 9 publications
(13 reference statements)
1
34
0
3
Order By: Relevance
“…Increasing unsaturation for a given chain length for both esters (methyl and ethyl) and triglycerides resulted in a decrease in the heat of combustion due to the loss of hydrogen. 68 The heat of combustion increases with increasing chain length and decreases with increasing unsaturation, 7,69,70 whereas fatty alcohols possess 55 Knothe et al 64 …”
Section: Heat Of Combustionmentioning
confidence: 98%
See 1 more Smart Citation
“…Increasing unsaturation for a given chain length for both esters (methyl and ethyl) and triglycerides resulted in a decrease in the heat of combustion due to the loss of hydrogen. 68 The heat of combustion increases with increasing chain length and decreases with increasing unsaturation, 7,69,70 whereas fatty alcohols possess 55 Knothe et al 64 …”
Section: Heat Of Combustionmentioning
confidence: 98%
“…(Continued) Source: Reproduced with kind permission from Freedman and Bagby 68. Copyright Ó 1989, American Oil Chemists' Society.…”
mentioning
confidence: 99%
“…i Empirical equations are available to predict gross heats of combustion (HG) [23] using the number of valence electrons (N ). j Empirical equations were used to calculate these quantities [23], and compared to those measured [14].…”
Section: Selection Of Field Sites: Pedogenic End-membersmentioning
confidence: 99%
“…Many attempts have hence been made to develop heating value prediction models based on experimental data. The HHVs of different biodiesel fuels have been measured and calculated by Freedman et al [19] and Krisnangkura [21] using a Parr adiabatic calorimeter according to ASTM D240 and D2015 standards. They developed a linear correlation between the heating value, carbon number and molecular weight, and they concluded that the HHV of biodiesel increased with increasing carbon number and molecular weight.…”
Section: Introductionmentioning
confidence: 99%